A Retrospective Cross-Sectional Study of Bone Marrow Pathology Among the Elderly Population - Debanjan Bhattacharjee; Soumya Kundu; Pamela Nayak (Annals of Pathology and Laboratory Medicine, 2026)
Background: India is experiencing a rapid demographic shift, with the elderly population (≥60 years) projected to reach 19.5% by 2050. This transition is accompanied by a rising burden of geriatric-specific hematological diseases, driven by age-related genetic alterations and comorbidities. Despite the clinical importance of bone marrow examination in diagnosing these complex conditions, comprehensive data from Eastern India remains sparse. This study aims to characterize the clinical profiles and determine the frequency of various bone marrow pathologies among elderly patients at a key tertiary care facility in West Bengal.Methods: A retrospective cross-sectional study was conducted in a tertiary care teaching hospital of West Bengal, covering a four-year period (2020–2023). The study included patients aged 60 years and above who underwent bone marrow aspiration (BMA) and/or trephine biopsy. Researchers re-evaluated all morphology slides and preserved paraffin blocks. Hematological neoplasms were classified according to the latest WHO criteria. Data analysis for frequency estimation was performed using MS-Excel. Result: Sixty cases were analyzed. Pancytopenia (51.67%) was the most common indication, followed by suspected leukemia (15%). Hypoplastic marrow was the most frequent diagnosis (21.67%; 95% CI: 13.1–33.6%). Primary haematological neoplasms accounted for 33.33% of cases, with acute myeloid leukemia and myelodysplastic neoplasm being the most common malignancies.Conclusion: This study provides critical regional data for Eastern India, emphasizing the high frequency of hypoplastic marrow and the necessity of integrated marrow morphology to navigate the complex hematological landscape of the aging population.